2013
DOI: 10.1103/physreva.88.022508
|View full text |Cite
|
Sign up to set email alerts
|

Quasipinning and entanglement in the lithium isoelectronic series

Abstract: The Pauli exclusion principle gives an upper bound of 1 on the natural occupation numbers. Recently there has been an intriguing amount of theoretical evidence that there is a plethora of additional generalized Pauli restrictions or (in)equalities, of kinematic nature, satisfied by these numbers [1]. Here for the first time a numerical analysis of the nature of such constraints is effected in real atoms. The inequalities are nearly saturated, or quasi-pinned. For rank-six and rank-seven approximations for lith… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
87
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(93 citation statements)
references
References 14 publications
6
87
0
Order By: Relevance
“…Only recently has the problem in the simplest case of m = 1 been solved [10], generalizing the equalities and inequalities in (1) systematically. This has led to a burst of studies of the relevance and implications of the so-called generalized Pauli constraints like (1) in atoms, molecules, and model systems [11][12][13][14][15][16][17][18][19][20]. As for the next case of m = 2 (which is possibly of more interest from the point of view of calculating the * wdlang06@163.com † mauser@courant.nyu.edu ground state energy of a multi-electron system), a systematic procedure for generating the N -representability conditions on the two-particle reduced density matrix has been derived by Mazziotti [21].…”
Section: Introductionmentioning
confidence: 99%
“…Only recently has the problem in the simplest case of m = 1 been solved [10], generalizing the equalities and inequalities in (1) systematically. This has led to a burst of studies of the relevance and implications of the so-called generalized Pauli constraints like (1) in atoms, molecules, and model systems [11][12][13][14][15][16][17][18][19][20]. As for the next case of m = 2 (which is possibly of more interest from the point of view of calculating the * wdlang06@163.com † mauser@courant.nyu.edu ground state energy of a multi-electron system), a systematic procedure for generating the N -representability conditions on the two-particle reduced density matrix has been derived by Mazziotti [21].…”
Section: Introductionmentioning
confidence: 99%
“…Such a configuration is in general favorable for the energy in comparison with other types of arrangements [6]. The 1-RDM (a 6 × 6 matrix) is the direct sum of two (3 × 3) matrices, one related to the spin up and the other related to the spin down:…”
Section: Exact Pinning In Spin-compensated Configurations For ∧ mentioning
confidence: 99%
“…In a seminal work, Borland and Dennis [2] observed that for the rank 6 approximation of a pure-state N = 3 system, belonging to the Hilbert space ∧ 3 H 6 , the occupation numbers satisfy the following additional conditions: n 1 + n 6 = n 2 + n 5 = n 3 + n 4 = 1 and n 4 n 5 + n 6 . The set of equalities allows exactly one electron in the natural orbitals r and 7 − r. The analysis by Klyachko and coworkers [3,4] of the pure N -representability problem for the 1-RDM establishes a systematical approach, generalizing this type of constraint.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The class of spin-compensated systems with time-reversal symmetry is a notable exception, since, in that case, the conditions for pure-state N -representability collapse to the ensemble conditions [32]. The necessary and sufficient conditions for pure-state N -representability, also called generalized Pauli constraints, have only recently been discussed and explicitly expressed for systems with a small number of particles and specific finite sizes of the Hilbert space [33][34][35][36][37][38][39]. Recently, it has been demonstrated that with enforcing only the ensemble conditions in a RDMFT calculation for open-shell systems, the pure-state conditions will be violated for many functionals of the 1RDM [40].…”
Section: Introductionmentioning
confidence: 99%